Effectiveness of acupoint hot compress on early puerperal rehabilitation of parturients after natural childbirth: study protocol for a prospective, multi-center, randomized controlled clinical trial - Yuhang Zhu; Aihua Zhang; Chang Liu; Nicola Robinson; Myeong Soo Lee; Xiaoyang Mio Hu; Hye Won Lee; Rong Zhang; Fan Qu (IMR Press, 2021)
Background: Early puerperal rehabilitation can interfere with a woman's ability to care for herself and her infant. Acupoint hot compress, with a combination of acupoints and natural physical agent heat, has significant potential to alleviate symptoms experienced during early puerperium. Current evidence regarding the effects of acupoint hot compress therapy on early puerperal rehabilitation is insufficient. The aim of this study is to address this with a multi-center design and large sample size. Methods: This is a prospective, multi-center, and randomized controlled clinical trial. A total of 1400 nulliparous women with a singleton pregnancy experiencing natural childbirth from 14 hospitals will be enrolled and randomly allocated to either an intervention group or a control group in a 1:1 ratio. Subjects in the control group will only receive routine postpartum care. In addition to routine postpartum care, the subjects in the intervention group will be administered a 4-hour acupoint hot compress with a constant temperature of 45 ± 2 ∘C respectively within 30 minutes after delivery, 24 hours and 48 hours after delivery. The primary outcome will be the time elapsed from delivery to the first urination. The secondary outcomes will be postpartum uterine contraction pain intensity, the Edinburgh Postnatal Depression Scale for screening postpartum depression and the assessment of lactation including recording the lactation initiation time, postpartum diet, appetite, weight, neonatal weight. Discussion: These results will provide evidence for obstetricians and parturients on considering nonpharmacologic and noninvasive intervention in early puerperal rehabilitation.